EFEKTIVITAS STRATEGI PEMBERIAN UMPAN BALIK TERHADAP KINERJA PRAKTIKUM MAHASISWA D-3 JURUSAN TEKNIK ELEKTRONIKA - Sapto Haryoko (Jurnal Cakrawala Pendidikan, 2011)
Abstract: Effectiveness of the Feedback Providing Strategies on the PracticumPerformance of the Students of the Diploma Three (D-3) of the ElectronicEngineering Department. This study aims to investigate the effectiveness of thefeedback providing strategies (immediate feedback and delayed feedback) onstudents’ performance in the Electronics lab course. This study was anexperiment employed a posttest-only control group design. The subjects werestudents of the Diploma Three (D-3) Program of the Electronic EngineeringDepartment of FT UNM, divided into two treatment groups. Group A,consisting of 20 students, received the treatment of the immediate feedback andGroup B, consisting of 19 students, received the treatment of delayed feedback.The data on the students’ mastery of lab materials were collected throughobservations using a performance assessment form. The data were analyzedusing the t-test. The results showed that the practicum performance of thestudents receiving immediate feedback was better than that of the studentsreceiving delayed feedback. Keywords: immediate feedback, delayed feedback, students’ practicum performance